2010
DOI: 10.1002/prep.200900065
|View full text |Cite
|
Sign up to set email alerts
|

Substituent Effects on Thermodynamic and Detonation Properties of Polynitrobenzenes

Abstract: Density functional theory (DFT) calculations were performed for a series of polynitrobenzene derivatives. Some nitrobenzenes with amino groups attached were also investigated as a benchmark or as a precursor. Heats of formation (HOF) were evaluated. The isodesmic reactions used for the prediction of HOFs are of permutation type in terms of the substituents. The HOFs increase non‐additively with increasing number of nitro groups. The attachment of the amino groups to polynitrobenzenes dramatically decreases the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The enthalpies of formation of nitro compounds were calculated earlier by different quantum chemical composite and DFT methods using the standard atomization reaction procedure and isodesmic reaction method. In our previous work, it was revealed that the G4 method, one of the most successful and widely used composite methods, underestimates the Δ f H 298 ° (g) values for most nitro compounds by up to 20 kJ·mol –1 . Therefore, reliable results cannot be expected when using the atomization reaction.…”
Section: Introductionmentioning
confidence: 99%
“…The enthalpies of formation of nitro compounds were calculated earlier by different quantum chemical composite and DFT methods using the standard atomization reaction procedure and isodesmic reaction method. In our previous work, it was revealed that the G4 method, one of the most successful and widely used composite methods, underestimates the Δ f H 298 ° (g) values for most nitro compounds by up to 20 kJ·mol –1 . Therefore, reliable results cannot be expected when using the atomization reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, a simple method, developed by Pang et al on the basis of the empirical Kamlet formula, was employed to calculate the heats of detonation of some metal-containing explosives (see ESI †). 58 The results showed Q for compound 1 to be 2.28 kcal g −1 , higher than those of most commonly used explosives, [59][60][61] including hexanitrohexaazaisowutzitane (CL-20; about 1.5 kcal g −1 ) 59,62 and octanitrocubane (ONC; 1.8 kcal g −1 ), 63 the two most powerful organic explosives known to date (see Chart 1). The findings imply that bridging carbonyl group is an effective and important energetic linker for constructing high-performance energetic materials with improved density, improved OB, suitable thermostability, high heat of formation and high energy.…”
mentioning
confidence: 98%